Electrical characterization of silicon PV- cell: modeling - Yahyaoui, Nejmeddine; Mansouri, Salaheddine; Al-Sehemi, Abdullah G.; Dere, A.; Al-Ghamdi, A.; Yakuphanoğlu, Fahrettin (Springer Heidelberg, 2024)
The photovoltaic properties of a monocrystalline silicon solar cell were investigated under dark and various illuminations and were modeled by MATLAB programs. According to AM1.5, the studied solar cell has an efficiency rate of 41-58.2% relative to industry standards. The electrical characteristics (capacitance, current-voltage, power-voltage, transient photovoltage, transient photocurrent, and impedance) of a silicon solar cell device were examined. Under complete darkness and light intensity of 100 mW/cm(2), respectively, we have noticed that the light of the AM1.5 spectrum changes all PV-cell parameters such as short current, open circuit voltage, maximum power, maximum voltage, and power conversion efficiency. An electrical equivalent circuit (R-1//C-1 + R-2//C-2) was used by the Zview software to fit the experimental data of the Nyquist representations (-Z'' vs. Z'). By analyzing the peak of the conductance G(p) versus frequency, the density of interface states and the interface trap time constant were calculated. By using MATLAB programs, we have modeled the current versus voltage and power versus voltage properties of equivalent solar cell circuits, ensuring a good agreement between the experimental and theoretical curves.
Keywords: Silicon solar cell; Nyquist diagram; Electricals characteristics; Matlab programs